Determinants of Trade Balance in Vietnam During 1997-2015 - Trung-Thanh To (Bright Institute, 2022)
This paper investigates the determinants of trade balance in Vietnam during 1997-2015, based on the restricted VECM model. The result suggests that in the long run, the openness has negative impact on trade balance. The initial level of NFA is negatively associated with trade balance. The more developed financial system can improve trade balance meanwhile higher income can worsen it. REER could have no close relationship with trade balance. Increasing FDI can contribute to trade deficit meanwhile capital mobility could improve trade balance. The trade balance also has a self-adjusting mechanism towards long-run equilibrium after the shocks to explanatory variables.